Evaluation of the awareness of pediatric residents of anaphylaxis diagnosis through clinical scenarios - Tülay Tuğçe Kutsal Gültekin, M.D.; Ayşe Gökçe Kutsal, M.D.; Gökhan Yörüsün, M.D.; Ahmet Selmanoğlu, M.D.; Kaan Çelebier, M.D.; Zeynep Şengül Emeksiz; Emine Dibek Mısırlıoğlu (World Allergy Organization Journal)
Introduction: Anaphylaxis is an acute onset, life-threatening systemic hypersensitivity reaction requiring urgent medical intervention. Early recognition and appropriate treatment of anaphylaxis are crucial for patient survival. This study aims to assess the awareness of pediatric residents regarding the diagnostic criteria, differential diagnosis, and appropriate treatment approaches for anaphylaxis. Materials and methods: Active pediatric residents volunteering in participating in the study were included. Participants were given a questionnaire consisting of 10 clinical scenarios assessing diagnostic criteria and 15 questions evaluating professional experience and knowledge. Results: A total of 198 pediatric residents were included in the study. The average clinical working experience of the participants was 18 months. On average, participants answered 7.3 out of 10 clinical scenario questions correctly (min-max: 3–10). In the clinical scenario describing a 2-year-old patient with a history of anaphylaxis to milk-based formula, the patient developed coughing and wheezing after entering the kitchen while the mother was boiling milk. The patient had a respiratory rate of 52/min, SpO2 of 90%, and bilateral wheezing. This case, which involved no ingestion and presented only with signs of bronchospasm, was the scenario that participants found most challenging. While 64.1% of the participants classified it as anaphylaxis, 35.9% identified that the clinical presentation did not meet the diagnostic criteria for anaphylaxis. Similarly, the scenario involving a 17-year-old patient with acute rheumatic fever who developed syncope 5 min after receiving a benzathine penicillin injection and presented with confusion, heart rate of 58 bpm, blood pressure of 80/50 mmHg, respiratory rate of 38 breaths/min, SpO2 of 95%, and sinus bradycardia on ECG, was the least correctly identified as vasovagal syncope in terms of a differential diagnosis of anaphylaxis (33.8%). The results indicated that pediatric residents were less successful in diagnosing anaphylaxis in cases without skin/mucosal involvement and in drug/venom-related anaphylaxis cases. When both scenario-based and knowledge-based questions were considered, residents in their final 2 years and those who had received specialist training demonstrated significantly higher overall correct response rates (p < 0.001, p = 0.002). Epinephrine was selected as the first-line treatment in 99.5% of cases; 81.3% of participants correctly identified the dosage, 97.5% the route of administration, and 89.4% the site of administration. Conclusion: In our country, the emergency treatment and follow-up of pediatric patients experiencing anaphylaxis are mostly carried out by pediatric specialists. Therefore, the education and training on the diagnosis and emergency management of anaphylaxis, a pediatric emergency, hold significant importance during the pediatric residency training period.